INTEGRATION OF VALUES WITH CONTENT TEACHING - BAGGA, NIRMAL (THE PRIMARY TEACHER, 2011)
Dr Radhakrishnan, a great educationist had said “Education should be man-making and society making”. Various spiritual and political leaders, educationists, philosophers, sociologists from time to time have also expressed their thoughts that education should enable a human being to attain the greatest harmony both internal and external. They also expressed that human potentialities and capacities must be developed to the fullest. Education should also make a man capable of earning his livelihood reasonably well to enjoy a happy life along with making effective contributions to the society and nation as a whole.